DINAMIKA KONFLIK AGRARIA DALAM PENYELESAIAN SENGKETA LAHAN: ANALISIS SOSIOLOGI HUKUM TERHADAP RELASI NEGARA, KORPORASI, DAN MASYARAKAT - Yusuf DM, Mohd.; Fadhli, M.; Saragih, Geofani Milthree; Santoso, Budi; Mulyono, Joko Dwi; Putra, Ari Armanda; Warianti, Khairunisak; Arifa, Atika Putri (Universitas Labuhanbatu, 2025)
This study aims to analyze the dynamics of agrarian conflicts in Indonesia using a sociological perspective on law, particularly in the context of land dispute resolution. This study uses a socio-legal approach by combining normative analysis of agrarian legislation and conceptual studies of legal sociology to understand the interaction between law, social structures, and power relations in the practice of land dispute resolution. The results show that the existence of agrarian regulations has not been fully able to realize substantive justice because their implementation is often influenced by social inequality, the dominance of economic interests, and the weak bargaining position of the community, especially farmers and marginalized groups. In practice, the law not only functions as a normative instrument but also reflects the configuration of power at work in society. Therefore, the resolution of agrarian conflicts requires an approach that is not merely legal-formal, but also sensitive to the social context, distributive justice, and the protection of land rights in a sustainable manner. Keywords: Agrarian Conflict; Sociology of Law; Land Disputes; Social Justice